The Impact of U.S. Foreign Aids on the Post-War Development of South Korea - Xing, Jingwen (Transactions on Social Science, Education and Humanities Research, 2024)
The United States mainly exerted influence on the stability of the Korean regime and the historical development of the Korean Peninsula from the two aspects of military and economic aid, thus enabling the post-war Korean society to establish rapid development into a capitalist country. The topic of this article is how Syngman Rhee's government shaped South Korea's postwar development through U.S. foreign aid during and after the Korean War. The actions and decisions of the U.S. and South Korean governments during and after the Korean War influenced the path of development in Korea. The study found that the United States has aided South Korea both militarily and economically. The reason South Korea receives aid is for national reconstruction, political stability, and economic stability. Syngman Rhee's government maximized the use of foreign aid for these three goals and established the authority of its political position while achieving social development in South Korea.